A SEMIOTIC ANALYSIS OF MEDIA MASS INTERNATIONAL (ARTICLE) ABOUT THE ISRAEL-PALESTINE CONFLICT ON OCTOBER 7, 2023 - Septiyani, Annisa (ReALL - Research on Applied Linguistics and Literature, 2024)
The Israel-Palestinian conflict has been going on for many years and being chaos again on October 7, 2023. This study aims to provide a deep understanding of how international media reported and interpreted the conflict through a semiotic analysis, The international media being analyzed are BBC, CNN, Al-Jazeera, and The New York Times. The research uses a qualitative method and focuses on news articles from these media that were uploaded on October 7, 2023. The semiotics analysis examines the denotative meaning, connotative meaning, and myth conveyed in the news article. The findings reveal how each article of the media constructs and represents the conflict, often with biases that shape public perception. This research reveals an important viewpoint on how the media influences public perceptions of the complicated geopolitical issues of the Israel and Palestine conflict. The result can help foster a more critical and knowledgeable discussion of how the media presents these issues.